2018
DOI: 10.3390/su10041144
|View full text |Cite
|
Sign up to set email alerts
|

Public Value of Enforcing the PM2.5 Concentration Reduction Policy in South Korean Urban Areas

Abstract: As the number of cars and the electricity produced from coal-fired generation has been increasing, PM 2.5 , particles smaller than 2.5 µm in diameter, has become a serious problem in South Korean urban areas. This is especially notable, given that the PM 2.5 warning was issued 89 times during 2016. Because of this, the South Korean government is seeking to enforce a policy of reducing the number of PM 2.5 warnings by half using various policy instruments from now until 2022. This article tries to obtain inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 29 publications
0
21
3
Order By: Relevance
“…For each set, four initial bids were chosen to produce "reasonably efficient and robust estimates" [38], the value of which was determined with reference to the findings from previous studies. According to Kim et al [9], the estimated mean WTP for enforcing PM 2.5 concentration reduction policy in Korea is KRW 5591 (USD 4.97) per household per year, whereas Wei and Luo [31] assessed an average WTP for PM 2.5 control in the Beijing-Tianjin-Hebei Region as CNY 65 (USD 9.47) per person per month. Therefore, initial bids for Korea started from KRW 5000 (USD 4.46) with an incremental amount of KRW 5000 for the next initial bid, and those for Chinese respondents started from CNY 20 (USD 2.91), with CNY 20 as the incremental amount for the next initial bid.…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For each set, four initial bids were chosen to produce "reasonably efficient and robust estimates" [38], the value of which was determined with reference to the findings from previous studies. According to Kim et al [9], the estimated mean WTP for enforcing PM 2.5 concentration reduction policy in Korea is KRW 5591 (USD 4.97) per household per year, whereas Wei and Luo [31] assessed an average WTP for PM 2.5 control in the Beijing-Tianjin-Hebei Region as CNY 65 (USD 9.47) per person per month. Therefore, initial bids for Korea started from KRW 5000 (USD 4.46) with an incremental amount of KRW 5000 for the next initial bid, and those for Chinese respondents started from CNY 20 (USD 2.91), with CNY 20 as the incremental amount for the next initial bid.…”
Section: Overviewmentioning
confidence: 99%
“…The number of PM 2.5 warnings issued (when the PM 2.5 concentration surpasses 90 µg/m 3 and stays over 2 h) has continued to increase, from 72 in 2015 to 92 in 2017 [8]. With the growing public concern about the related health impact, PM 2.5 has turned into a big social issue in Korea [9]. The Korean government has taken various mitigation and responsive actions to deal with the PM 2.5 issue.…”
Section: Introductionmentioning
confidence: 99%
“…For decades, particulate matters with aerodynamic diameters less than 2.5 micrometers (PM2.5) have attracted significant attention in the Republic of Korea. According to the Ministry of Environment, the national average concentration of PM2.5 increased from 28 µg/m 3 in 2015 to 30 µg/m 3 in 2016, and reached 31 µg/m 3 in 2017 [1] which is three times higher than the World Health Organization (WHO) annual guideline(10 µg/m 3 ) [2]. Various environmental epidemiology studies have identified significant positive associations between exposure to airborne PM2.5 and the exacerbation of chronic or acute disease symptoms [3,4], increased mortality risk [5], decreased life expectancy [6], and low birth weight [7].…”
Section: Introductionmentioning
confidence: 99%
“…Second, the interval of sets of bids becomes larger. This method, proposed by Cooper et al [36], is a common practice in the one-and-one-half-bounded (OOHB) dichotomous choice (DC) question method. Thus, this article followed this method proposed by Cooper et al [37].…”
Section: Sampling and Survey Questionnairementioning
confidence: 99%
“…The authors sorted the reported positive values in ascending order, trimmed 10% of observations from both tails, and determined seven bids from the trimmed distribution in a manner of increasing interval. Seven sets of bids are widely used in various papers (e.g., [20,36]). Thus, we followed previous papers and used seven sets of two bids, determined through a pretest of a focus group.…”
Section: Sampling and Survey Questionnairementioning
confidence: 99%